Performance of constructed wetlands using Vetiveria zizaniodes for sewage treatment - Ahmad, Noraziah (2010)
Sewage is one of the major problems to overcome in managing the domestic sewage. Treatment that low cost, need less maintenance and environmental friendly are among target on how to treat the domestic sewage. This research was focused on the capability of the Vetiveria zizaniodes plant to remove pollutant through the constructed wetland. The study carried out through two type HRT systems, which were HRT-5 and HRT-0. The constructed wetlands were planted with Vetiveria zizanoides in different population for every cell which is cell control, less population and more population. The efficiency of the systems to reduce the concentration of oil and grease, ammoniacal nitrogen (NH3-N), Biochemical Oxygen Demand (BOD), total suspended solid (TSS), and orthophosphate (PO43-) were analyzed. The performance of dissolved oxygen (DO) and pH are also considered. From the study it was found that the constructed wetlands using Vetiveria zizaniodes is significantly contributed in removal efficiency of BOD, orthophosphate and ammoniacal nitrogen on HRT-5 while on HRT-0 it’s contributed in removal efficiency of TSS. The results showed the ability of constructed wetland using the Vetiveria zizaniodes to reduce up to 56% of ammoniacal nitrogen removal, 79% of orthophosphate, 53% of BOD and 51% oil & grease after 7 days of treatment for HRT-5. On the other side wetland was able to remove 62% of TSS after end of experiment for HRT-0 on day 7 of treatment. It can be conclude that Vetiveria zizaniodes posed a great role in removing orthophosphate, ammoniacal nitrogen, BOD, TSS and oil and grease in different hydraulic retention time.